2015
DOI: 10.3892/etm.2015.2829
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal capsaicin treatment in rats induces chronic hyperthermia resulting in infectious disease

Abstract: Treatment of neonatal animals with capsaicin has previously been associated with long-lasting hyperthermia and severe cutaneous lesions. The present study analyzed the effects of capsaicin-induced hyperthermia on the occurrence of infectious disease and pruritic dermatitis in a rat model. Pregnant Sprague-Dawley (SD) rats were obtained 1 week prior to parturition. Pups from each litter were randomly assigned to the following experimental groups: Capsaicin-treated (cap-treated; n=10) or vehicle-treated (n=5). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The difference between TRPV1 antagonist and neonatal capsaicin treatment is that the hyperthermic effect of capsaicin treatment in neonates is long-lasting [10]. Previous studies on body temperature changes following topical or neonatal capsaicin treatment are listed in Table 3 [13,[38][39][40][41]. Numerous studies have been carried out on the analysis of the effect of hyperthermia on immune cell subsets targeting the tumor, and upregulation of interleukin induced T lymphocyte proliferation by TRPV-1 activation was found to be increased by hyperthermia [42].…”
Section: Changes In Body Temperature and Exposure To Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The difference between TRPV1 antagonist and neonatal capsaicin treatment is that the hyperthermic effect of capsaicin treatment in neonates is long-lasting [10]. Previous studies on body temperature changes following topical or neonatal capsaicin treatment are listed in Table 3 [13,[38][39][40][41]. Numerous studies have been carried out on the analysis of the effect of hyperthermia on immune cell subsets targeting the tumor, and upregulation of interleukin induced T lymphocyte proliferation by TRPV-1 activation was found to be increased by hyperthermia [42].…”
Section: Changes In Body Temperature and Exposure To Infectionmentioning
confidence: 99%
“…Activation of TRPV1 expressed in sensory neurons leads to inflammatory diseases, such as bronchoconstriction, tracheal mucosal edema, and inflammatory cell chemotaxis [45]. A related study on neonatal capsaicin treatment indicated that induction of constant and permanent hyperthermia in the body might induce an abnormal physiological function related to the body defence system [13]. Brown adipose tissue present in human and animal newborns is responsible for maintaining body temperature and is essential for thermogenesis.…”
Section: Changes In Body Temperature and Exposure To Infectionmentioning
confidence: 99%
See 3 more Smart Citations